2004
DOI: 10.1021/cg049812n
|View full text |Cite
|
Sign up to set email alerts
|

Superadhesion:  Attachment of Nanobacteria to Tissues − Model Simulation

Abstract: Adhesion is common in the bacterial world and is partially mediated by slime. Nanobacteria (NB) seem to attach by slime as well as by the protecting nanocrystalline apatite shell, securing their survival in hostile milieus. Identification of NB in the human heart has brought the particles into the focus of material scientists. In view of the size distribution of the apatite nanovesicles (80-300 nm), simulation of their interaction with tissues can be performed via nanosuspensions and mirror-polished titanium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Regardless of the aqueous phase matrix, the aggregates of hemoglobin, once dried, coated and studied by SEM, all had the same appearance. These inert structures resemble the images of nanobacteria found in diseased hearts, kidneys, and the urine of HIV patients, as well as in cancer tissue (1,3,4,(11)(12)(13)15).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Regardless of the aqueous phase matrix, the aggregates of hemoglobin, once dried, coated and studied by SEM, all had the same appearance. These inert structures resemble the images of nanobacteria found in diseased hearts, kidneys, and the urine of HIV patients, as well as in cancer tissue (1,3,4,(11)(12)(13)15).…”
Section: Resultssupporting
confidence: 61%
“…In a separate study, synovial fluids from diseased knee joints were allowed to sit for two months and nanobacteria propagated with most having a spherical shape less than 2 micrometers in diameter (11). A study done at autopsy of an individual with atherosclerosis supports, but does not prove, that nanobacteria contributed to its pathogenesis (12). It has also been reported that nanobacteria anchor themselves in aqueous environments in the body by slime and produce a nano-crystalline apatite shell.…”
mentioning
confidence: 99%
“…If it is not possible to eliminate dormant NB by some means prior to departure, the use of low-level laser light or LED arrays with intensities around the solar constant within the spacecraft may prove a useful option to alleviate the potentially hazardous effects of space travel. Our recommendation derives support from two recent developments: the identification of NB in the terrestrial atmosphere [14], confirming a previously formulated hypothesis regarding their atmospheric prevalence [15] and model simulations indicating a strong bioadhesive capacity of NB [12].…”
supporting
confidence: 86%
“…12 Interestingly, the pathogenic nature of NB can be traced back solely to the synergistic interplay of the first two properties. [13][14][15] Conversely, therapies to reduce concentrations of NB in the body could be derived from the last two properties. [16][17][18] This becomes clear by realizing that without the protein based slime, the bioadhesive capacity of NB must decrease.…”
Section: Introductionmentioning
confidence: 99%